The performance of male duck fed different levels of crude palm oil - Bintang, I.A.K; Tangendjaja, Budi (Indonesian Animal Sciences Society, 1996)
An experiment was conducted to evaluate the optimum level of inclusion of crude palm oil (CPO) in ducks diet . The treatments consisted of 5 different levels ofCPO (0, 5, 10, 15 and 20%) with 5 replicates and 10 day-old ducks/replicate. The ducklings were allocated in litter system covered with rice hull . At 0-3 weeks old, ducklings were fed with starter commercial diet . The experiment diet was given to starter (3 - 5 weeks old) and to grower (5-8 weeks old) ducks containing crude protein 19 .5 and 17%, respectively and metabolizable energy 2,900 kcal/kg. Measurements done were on body weight, feed consumption, carcass weight, internal organ and abdominal fats . There were no significant difference among treatments on body weight gain, feed consumption, feed conversion, carcass or internal organ weight . There was an increase on abdominal fat with an increase level ofCPO in the diet. Male duck had the ability to accept up 20% CPO in the diet without any negative effect. Â Key words: Performance, male duck, crude palm oil